Double sampling X̄ control chart for a first order autoregressive process - Claro, Fernando A. E. [UNESP]; Costa, Antonio F. B. [UNESP]; Machado, Marcela A. G. [UNESP] (FapUNIFESP (SciELO), 2008)
In this paper we propose the Double Sampling X̄ control chart for monitoring processes in which the observations follow a first order autoregressive model. We consider sampling intervals that are sufficiently long to meet the rational subgroup concept. The Double Sampling X̄ chart is substantially more efficient than the Shewhart chart and the Variable Sample Size chart. To study the properties of these charts we derived closed-form expressions for the average run length (ARL) taking into account the within-subgroup correlation. Numerical results show that this correlation has a significant impact on the chart properties.
Keywords: Autocorrelation; Double Sampling; Statistical process control